2007
DOI: 10.1124/dmd.107.016014
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Intracellular Concentration Causes the Shift in Km Value of Efflux Pump Substrates

Abstract: ABSTRACT:Passive permeability and active efflux are parallel processes in transcellular flux. Therefore, the observed kinetics of a transporter substrate depends on both of these factors. The transporter expression has been shown to affect both the apparent K m and V max values. Kinetic parameters can be obtained from various experimental settings, but these do not necessarily reflect the situation in transcellular flux. Kinetic absorption models need reliable estimates of saturable kinetics when accurate in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 27 publications
1
48
2
Order By: Relevance
“…It is interesting to notice that in the study from Balimane et al [187] , the A-B transport data gave more stringent IC50 values than the B-A transport data, when the opposite was the case for the deduction of Km by others. [188,189] A more stringent IC50 value from the A-B data may be explained by a lower apical permeability of the probe substrate thus limiting its intracellular concentration. Consequently, a lower concentration of the drug substance (acting as an inhibitor) is required for the inhibition of the efflux transporter.…”
Section: Transcellular Transport Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…It is interesting to notice that in the study from Balimane et al [187] , the A-B transport data gave more stringent IC50 values than the B-A transport data, when the opposite was the case for the deduction of Km by others. [188,189] A more stringent IC50 value from the A-B data may be explained by a lower apical permeability of the probe substrate thus limiting its intracellular concentration. Consequently, a lower concentration of the drug substance (acting as an inhibitor) is required for the inhibition of the efflux transporter.…”
Section: Transcellular Transport Studiesmentioning
confidence: 99%
“…In addition, it has been shown that Km values deducted with basis in extracellular drug concentrations are dependent on the expression levels of the efflux transporter, since an increased efflux capacity due to a high expression level will result in a lower intracellular drug concentration. [189,194] Hence, it is not surprising, that kinetic constants differ greatly between in-vitro systems for the human efflux transporter P-gp even though the same calculation method was applied, as the results are dependent on both influx permeability and expression level of the transporter. [30,189,194,195] In addition to the above presented drawbacks in using Michaelis-Menten kinetics for estimating drug affinity for efflux transports, the interpretation of transcellular transport data across a double-membrane as if they were from a singlemembrane system, has been criticized also.…”
Section: Limitations Of In-vitro Determined Kinetic Parameters For Trmentioning
confidence: 99%
See 3 more Smart Citations